2017
DOI: 10.1139/facets-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

A paleolimnological archive of metal sequestration and release in the Cumberland Basin Marshes, Atlantic Canada

Abstract: We used a paleolimnological approach at Long Lake, Nova Scotia, to construct a 10 500-year record of metal deposition in lakebed sediments and elucidate the influence of both natural and anthropogenic environmental changes. Aquatic sediment concentrations of mercury (Hg), arsenic (As), and chromium (Cr) in Long Lake fluctuated substantially and, during some periods, exceeded guidelines for the protection of aquatic life. Increases in lead (Pb), Hg, Cr, trace metals, and nitrogen stable isotopes (δ 15 N) were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 63 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Nriagu 1990; Health Canada 2013), then subsequently declined due to the phase out of leaded gasoline (Cheyne et al 2018; Dunnington et al 2020). Furthermore, we examined concentrations of aluminum (Al; an inert metal in mineral sediments), which we plotted against Pb concentrations (ratio of Pb/Al) to normalize for flood events that could increase the deposition of trace metals through minerogenic influxes (Dunnington et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Nriagu 1990; Health Canada 2013), then subsequently declined due to the phase out of leaded gasoline (Cheyne et al 2018; Dunnington et al 2020). Furthermore, we examined concentrations of aluminum (Al; an inert metal in mineral sediments), which we plotted against Pb concentrations (ratio of Pb/Al) to normalize for flood events that could increase the deposition of trace metals through minerogenic influxes (Dunnington et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Wildfires consume organic matter and redistribute metals accumulated therein on the landscape by two pathways, the atmospheric transport of fly ash and volatile compounds and the hydrological transport of ash, leachates and charred material from burned catchment. Multiple studies based on paleolimnology (Dunnington et al, 2017;Kristensen & Taylor, 2012;Kristensen et al, 2017;Odigie et al, 2015; or ground-based measurements (Burton et al, 2016;Cerrato et al, 2016;Pompeani et al, 2020;Stein et al, 2012) have shown evidence of excess loading of Hg, Pb As, Cr, Mn, and Zn in streams and lakes at close distance to recent wildfires.…”
Section: Wildfires As a Remobilising Agent For Anthropogenic Metal Pollutantsmentioning
confidence: 99%